Acute Urinary Retention and Obstructive Uropathy Secondary to Imperforate Hymen in a Premenarchal Adolescent: A Comprehensive Case Report - Siti Dian Meylani; Hervyasti Purwiandari; Ernawati (HM Publisher, 2026)
Background: Imperforate hymen, occurring in approximately 1 in 1,000 to 1 in 10,000 female births, is a rare congenital anomaly of the female reproductive tract that frequently remains undiagnosed until menarche. It can present atypically as acute urinary retention due to mechanical pelvic compression. Case presentation: A 12-year-old premenarchal girl presented to the emergency department with an 8-hour history of acute urinary retention, cyclic lower abdominal pain, and nausea. Her history revealed a 4-month progression of dysuria and painful defecation. Physical examination demonstrated a bulging, bluish vaginal membrane. Transabdominal ultrasonography revealed a 520 mL hematocolpos severely compressing the bladder neck, resulting in bilateral mild hydroureteronephrosis. The variance between the imaging estimate (520 mL) and the actual surgical yield (480 mL) reflects standard clinical overestimation in ultrasonographic volume calculations. The patient underwent an emergency cruciate hymenotomy with mucosal marsupialization. Postoperative recovery was uneventful. A 3-month follow-up confirmed the complete resolution of the hydroureteronephrosis and the establishment of normal, unobstructed menses. Conclusion: Delayed diagnosis of imperforate hymen can precipitate severe obstructive uropathy. Integrating routine external genitalia examinations in premenarchal adolescents presenting with lower urinary tract symptoms is imperative to prevent irreversible urological sequelae.